TINGKAT PENGETAHUAN IBU MENETEKI MEMPENGARUHI PEMILIHAN JENIS KONTRASEPSI SUNTIK DI PUSTU KANGENAN PAMEKASAN - Nurul Kamariyah (Jurnal Ilmiah Kesehatan, 2015)
Contraceptive injection acceptors in Pamekasan District have reached 66.85%. The appropriate type of contraceptive injection for the breastfeeding mothers is the three-month injection because it doesn’t disturb the lactation process. In Pustu (supporting community health center) Kangenan, almost all breastfeeding mothers choose one-month contraceptive injection. The influencing factor for them to choose the contraceptive injection is knowledge. Therefore, this research was purposed to find out the relationship between the breastfeeding mothers’ knowledge and their choice for contraceptive injection.    The design of this research was analytic-observational done by applying the cross sectional approach. The population involved 48 breastfeeding mothers choosing the contraceptive injection. The samples included the simple random sampling involved 42 respondent The research done in July 2014 used the instrument of questionnaire and LPD (data collection sheet). The result of the research showed that among 23 respondents with low level of knowledge, almost all of them (78.3%) chose one-month contraceptive injection (cyclofem) which didn’t meet their needs. Moreover, the result of data analysis using SPSS program for Windows and Mann-Whitney test revealed that ρ= 0.003 < α 0.05 which proved that there was a relationship between the breastfeeding mothers’ knowledge and their choice for contraceptive injection.      The conclusion of this research was that the breastfeeding mothers’ knowledge and their choice for contraceptive injection were related. Hence, the breastfeeding mothers should choose the three-month contraceptive injection because it gives no influence to the breast milk. Besides, the maximum counseling should also be done to the forthcoming acceptors to choose the appropriate contraceptive method.